The Length-Biased Wieghted Kpendidum Distribution: Properties and some Real-Life Applications - Z. Ahmood, Ranen; Al-Sabbagh, Akram; A. Ameen, Haneen (Al-Nahrain Journal of Science, 2026)
The main aim of this paper is to introduce a new class of one-parameter statistical models namely the length-biased weighted Kpendidum distribution. This distribution is a convex combination of three component of Gamma distribution. Some statistical and reliability properties of this distribution are discussed. The maximum likelihood estimation is used to estimate the one-parameter of the presented distribution. Moreover, five real life applications are provided to investigate the effectiveness of the new model in comparison with the Kpendidum distribution and some other one-parameter length-biased weighted models. Additionally, it is shown that in some real-life applications the proposed model gives a better results than some of the two-parameter models. Finally, different statistical measures are used to guarantee the accuracy of this model.